Prospect for nuclear engineering education in Malaysia - Alang Md Rashid, Nahrul Khair; Daud, Ainul Hayati (2009)
The use of nuclear power for electricity generation using nuclear power reactors are well-known. Malaysia is considering the use of nuclear power in her energy mix. Engineers with nuclear engineering background will be needed alongside other engineering disciplines. The planning window for a national nuclear power program is long, but the need to graduate nuclear engineers from Malaysian universities should be thought about earlier. There are courses in Malaysian universities that are related to nuclear science and technology. These courses are far from typical nuclear engineering curriculum, but can be the basis for setting-up such program. The nuclear program is not expected to be very big as to require multiple universities offering nuclear engineering degree program. Furthermore suitable faculties are dispersed among several universities. Consortium of universities could be an approach to start the human capital aspect of the nuclear power program.